2021
DOI: 10.3389/fonc.2021.712786
|View full text |Cite
|
Sign up to set email alerts
|

Long Non-Coding RNAs in Diagnosis, Treatment, Prognosis, and Progression of Glioma: A State-of-the-Art Review

Abstract: Glioma is the most common malignant central nervous system tumor with significant mortality and morbidity. Despite considerable advances, the exact molecular pathways involved in tumor progression are not fully elucidated, and patients commonly face a poor prognosis. Long non-coding RNAs (lncRNAs) have recently drawn extra attention for their potential roles in different types of cancer as well as non-malignant diseases. More than 200 lncRNAs have been reported to be associated with glioma. We aimed to assess … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 261 publications
0
29
0
Order By: Relevance
“…LncRNAs are increasingly being investigated for their role in diagnosis, prognosis and treatment of cancers ( 6 ), including gliomas ( 7 ). They are also being investigated for possible role in determining resistance against therapies ( 8 , 9 ), including in gliomas ( 8 , 10 ).…”
Section: Introductionmentioning
confidence: 99%
“…LncRNAs are increasingly being investigated for their role in diagnosis, prognosis and treatment of cancers ( 6 ), including gliomas ( 7 ). They are also being investigated for possible role in determining resistance against therapies ( 8 , 9 ), including in gliomas ( 8 , 10 ).…”
Section: Introductionmentioning
confidence: 99%
“…LncRNAs play crucial regulatory roles in modulating the cell cycle, cell proliferation, cell invasion, and migration by regulating gene expression at the transcriptional, post-transcriptional, and epigenetic levels ( 6 , 7 ). Studies have demonstrated that dysregulation of lncRNA expression is related to gliomas tumorigenesis and cancer progression and that it is a potentially effective early diagnostic, prognostic biomarker, and therapeutic target ( 8 ). However, the specific and detailed molecular mechanisms underlying the involvement of lncRNAs in glioma carcinogenesis and progression remain largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies have indicated that lncRNAs are composed of promoter regions, exons, antisense sequences, enhancer sequences, 3′- and 5′-UTRs, introns, and intergenic and intragenic regions of the genome. LncRNAs have key roles in physiological activities, including epigenetic regulation, cell cycle regulation and cell differentiation regulation through multiple pathways and mechanisms ( 98 ). These RNAs have become a focus of genetic research.…”
Section: Lncrnas and Glioma Drug Resistancementioning
confidence: 99%
“…These RNAs have become a focus of genetic research. More importantly, lncRNAs have been indicated to serve as biomarkers for the diagnosis, treatment, prognostication, drug response prediction and other pathological processes of gliomas by interacting with miRNAs to form a competing endogenous RNA (ceRNA) network, participating in histone modification and directly binding to target genes ( 98 ). In this chapter, the roles of related lncRNAs in the development of chemotherapy resistance in gliomas are discussed and a sufficient theoretical basis for the comprehensive understanding of the mechanisms of tumour drug responses are provided.…”
Section: Lncrnas and Glioma Drug Resistancementioning
confidence: 99%